(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This study aims to find out a descriptive description of the implementation of governance in the management of village funds which will ultimately affect the implementation of village governance. This research is a qualitative research with primary data and secondary data. Primary data obtained through observation, interviews and documentation. Secondary data using literature study. As for the results of the research conducted, it shows that the management of village fund budgets must be based on the principles of Good Governance in the village whose management is a whole activity covering the stages and processes that have been regulated, namely the initial activity is the participatory planning stage, the implementation that meets transparency, and accountability processes for village fund budgets (ADD)